2018
DOI: 10.3390/catal8050200
|View full text |Cite
|
Sign up to set email alerts
|

Improvement Effect of Ni to Pd-Ni/SBA-15 Catalyst for Selective Hydrogenation of Cinnamaldehyde to Hydrocinnamaldehyde

Abstract: Abstract:A series of Pd-Ni bimetallic catalysts supported on SBA-15 (0.2%Pd-x%Ni/SBA-15, x = 0.4, 0.7, and 1.2) were prepared through the impregnation method combined with the NaBH 4 reduction method. X-ray diffraction (XRD), N 2 adsorption-desorption, X-ray photoemission spectroscopy (XPS) and transmission electron microscope (TEM) were used to characterize the prepared catalysts. All the synthesized catalysts were evaluated for the liquid-phase hydrogenation of cinnamaldehyde (CAL). The addition of Ni obviou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(5 citation statements)
references
References 66 publications
0
5
0
Order By: Relevance
“…Compared to various Pd catalysts, the Pd/C catalysts reduced by CO molecules in this study showed the highest activity and comparable high selectivity (Table S6). , …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Compared to various Pd catalysts, the Pd/C catalysts reduced by CO molecules in this study showed the highest activity and comparable high selectivity (Table S6). , …”
Section: Resultsmentioning
confidence: 99%
“…The Pd catalyst has high activity and selectivity toward the hydrogenation of the CC bond of an α, β-unsaturated aldehyde such as CAL . To increase selectivity in the hydrogenation of the CC bond, control the Pd particle size, and tune the Pd electronic state by alloying with the second metal, , metal–support interactions have been conducted . In contrast, the morphology of Pd particles is also considered to be an important factor for CAL hydrogenation.…”
Section: Introductionmentioning
confidence: 99%
“…For example, a MCM-41 supported Pd−Ag alloy catalyst was applied for hydrogenation of CAL, and 98.6% of HCAL selectivity, with almost 100% CAL conversion, was achieved due to the ultrasmall Pd particle size and geometric and electronic effect between Pd and Au. 5 In addition to Ag, tungsten nitride (WN), 90 Ni, 91 and Sn 92 were also used as promoters for Pd catalysts. As shown in Table 3, entries 23− 25, 0.2%Pd-1.2%Ni/SBA-15 catalyst showed the highest selectivity to HCAL at a 12 bar H 2 pressure.…”
Section: Catalyst Design Strategy For Selective Hydrogenation Of Calmentioning
confidence: 99%
“…No discernable diffraction peaks at 2θ = 40.08°, 46.62° assigned to (111), (200) reflections of Pd lattice [35] can be detected for all catalysts because of the high dispersion of Pd species [36] and low Pd loading (1 wt%). 2a, all catalysts exhibit typical type IV isotherms and H1 type hysteresis loops at the relative pressure P/P 0 between 0.7 and 0.85, indicating the presence of cylindrical channels with ordered pore structure [37,38]. Figure 2b demonstrates the narrow and uniform pore size distributions with the pore diameter of around 8 nm.…”
Section: Xrdmentioning
confidence: 90%